Management Instruments for New Product Development (NPD), Customers' Satisfaction and Loyalty - Luqman Arshad (iRASD Journal of Management)
The objective of this paper is to examine the existing body of knowledge regarding the introduction of new products to the market, along with the factors that contribute to the launch's success. Considerable research has been devoted to examining the successes and failures of novel product development. The majority of these articles have employed the benefits point of product features and development methodology in their investigations. This article presents an analysis of the results obtained from a comprehensive collection of research that examines the factors that impact achievement. Conversely, we analyze the product through the lens of the launch support program. In order to offer an empirical response to the question of whether successful consumer product launch decisions vary, we begin by conducting a comparative analysis of the consumer product development process leading up to launching decisions across various market types. In regards to consumer goods, strategic launch decisions appear to be more defensive, as they prioritize the preservation of current market positions. As a result of leveraging technology and innovation to expand into new markets and operate beyond their current scope of operations, consumer goods strategy launch decisions appear to be more assertive than in the past. Furthermore, the determinations pertaining to the implementation of the tactical marketing mix (comprising product, place, promotion, and pricing) vary considerably among the newly introduced products.